THU0377 MIR-29C in Urinary Exosomes as Predictor of Early Renal Fibrosis in Lupus Nephritis. (9th June 2015) - Solé-Marcé, C.; Cortés-Hernández, J.; Vidal, M.; Felip, M.L.; Ordi-Ros, J.
Abstract : Background: Despite overall improvement in prognosis, 10-30% of patients with lupus nephritis (LN) will develop End-Stage Renal Disease [1]. To date, renal biopsy is still the gold standard test used to predict renal outcome. However, due to its invasive nature, new non-invasive biomarkers are required. The anti-fibrotic effects of microRNA-29c may be result of its ability to inhibit TGF-β/Smad3-mediated deposition of extracellular matrix (ECM) [2]. Urinary exosomes, microvesicles released by every epithelial cell facing the urinary space, represent an ideal source of markers for renal dysfunction and injury. Objectives: Here we sought to evaluate miR-29c expression levels in urinary exosomes as a novel biomarker of renal fibrosis in LN and study the relation between the expression of miR-29c and genes related with TGF-B pathway to investigate more about the mechanism of renal fibrosis in lupus nephritis. Methods: Urinary exosomes were isolated from 28 patients with biopsy-proven LN and 20 healthy controls. Electronic microscopy and western blot were used to characterize the exosomes. Expression levels of miR-29c were detected by RT-PCR quantitative and correlated with clinical and histological parameters along with the expression levels of Smad2/3, TGF-β and MMP2/9. For comparison, miRNA expression was also evaluated in the urinary pellet. Results: MiR-29c levels in urinary exosomes showed a negatively strong correlation with the histological chronicity index (r=-0.898, p=0.001) and glomerular sclerosis (r=-0.555, p=0.007). No correlation with eGFR and creatinine levels was found. MiR-29c expression levels could predict the degree of chronicity in patients with LN with an area under the curve (AUC) of 0.946 (p<0.001) and with high sensitivity and specificity (94% and 82%). Smad3 and MMP2 expression in urinary exosomes correlated negatively with miR-29c expression (r=-0.737 and -0.856 respectively). In the urinary pellet, no miR-29c expression was detected; however, upregulation of Smad3 and MMP2 was observed (3.54 and 5.85 fold increase). Conclusions: Overall, miR-29c correlated with the degree of renal chronicity but not with renal function, suggesting it could be used as a novel non-invasive marker of early progression to fibrosis in patients with LN. References: Fiehn C. Early diagnosis and treatment in lupus nephritis: how we can influence the risk for terminal renal failure. J Rheumatol 2006; 33:1464–1466. Qin W. et al. TGF-/Smad3 signaling promotes renal fibrosis by inhibiting miR-29. J Am Soc Nephrol 2011; 22:1462-1474. Disclosure of Interest: None declared